2020
DOI: 10.1088/1361-6528/ab647b
|View full text |Cite
|
Sign up to set email alerts
|

Al-based metal organic framework derived self-assembled carbon nanosheets as innovative anodes for Li- and Na-ion batteries

Abstract: Al-based MOF derived self-assembled carbon nanosheets as innovative anodes for Li-and Na-ion batteries

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 38 publications
2
6
0
Order By: Relevance
“…With increasing pyrolysis temperature, the SSA first increased from 1321.0 to 1571.4 m 2 g −1 (600-700 °C), then decreased to 465.1 m 2 g −1 (at 1000 °C). [157] The same phenomenon has been observed for ZIF-8-derived nitrogen-doped porous carbons, where the largest SSA (>600 m 2 g −1 ) has been realized at a pyrolysis temperature of 700 °C. [140] The considerable low SSA for the sample derived at 600 °C (349.9 m 2 g −1 ) can be attributed to the less well developed pores as a result of insufficient (b) the XPS N 1s spectra of NPC-500, NPC-600, and NPC-700.…”
Section: Pore Structure Designsupporting
confidence: 63%
See 1 more Smart Citation
“…With increasing pyrolysis temperature, the SSA first increased from 1321.0 to 1571.4 m 2 g −1 (600-700 °C), then decreased to 465.1 m 2 g −1 (at 1000 °C). [157] The same phenomenon has been observed for ZIF-8-derived nitrogen-doped porous carbons, where the largest SSA (>600 m 2 g −1 ) has been realized at a pyrolysis temperature of 700 °C. [140] The considerable low SSA for the sample derived at 600 °C (349.9 m 2 g −1 ) can be attributed to the less well developed pores as a result of insufficient (b) the XPS N 1s spectra of NPC-500, NPC-600, and NPC-700.…”
Section: Pore Structure Designsupporting
confidence: 63%
“…MOF-Derived Carbon: Several studies have shown that BET surface areas and pore sizes of MOF-derived carbons can be feasibly modulated by altering pyrolysis temperatures, thereby controlling their LIB performance. [157,161,262] For example, porous carbon NSs have been prepared by sequential pyrolysis and acid etching of Al-MOFs (denoted as PCNS-n, n represents the pyrolysis temperature). [157] With rising temperature, both the S BET and total volume (V tot ) increase and then decrease (reaching the maximum value for PCNS-700, i.e., 1571.4 m 2 g −1 and 1.78 cm 3 g −1 ).…”
Section: Engineering Of Pore Structuresmentioning
confidence: 99%
“…[132][133][134][135] Many MOFs have been reported so far as Li-cathodes. 55,136,137 Similar Li-based battery MOFs have been reported in non-Lithium batteries too. For instance, in our previous work, we investigated Metal Organo-Phosphate Open Frameworks (MOPOFs) as cathode materials for Li-ion batteries.…”
Section: Mof As Cathode Materials For Various Energy Storage Modessupporting
confidence: 62%
“…For instance, Zeng et al, have reported the use of carbon nanosheets derived from the self-assembled Al-MOF, which exhibited 193 mA h g À1 capacity after 100 cycles when tested at 100 mA g À1 for Na-ion battery applications and at a high rate of 1000 mA g À1 ; the MOF-derived carbon delivered a specific capacity of 109.5 mA h g À1 over 3500 cycles. 55 In their work, MOF-derived carbon materials were functionally modified with a desired structure in order to improve the charge capacity. The solvothermal method was used to induce the self-assembly of the MOF, followed by carbonization and acid treatment to remove the metal nodes from the framework.…”
Section: Batteriesmentioning
confidence: 99%
See 1 more Smart Citation